1993
DOI: 10.1093/oxfordjournals.molbev.a040079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the major outer-membrane protein (MOMP) gene of mouse pneumonitis (MoPn) and hamster SFPD strains of Chlamydia trachomatis with other Chlamydia strains.

Abstract: Restriction fragments containing the major outer-membrane protein (MOMP) gene from two nonhuman (rodent) strains of Chlamydia trachomatis, the mouse pneumonitis (MoPn) strain and the SFPD strain isolated from hamsters with transmissible proliferative ileitis, were cloned and sequenced. The MOMP genes of both MoPn and SFPD encode an identical 22-amino acid leader peptide and mature polypeptides of 365 and 382 amino acids, respectively. Alignment of the MOMP genes of the two rodent strains revealed 91% identity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The 16S rRNA and ompA genes have been extensively used to distinguish and phylogenetically group chlamydial species [24][27]. Although not as informative as our newly identified target genes, our analysis showed that 16S rRNA, ompA and omcB were evolving in much the same way as our target genes.…”
Section: Resultsmentioning
confidence: 69%
“…The 16S rRNA and ompA genes have been extensively used to distinguish and phylogenetically group chlamydial species [24][27]. Although not as informative as our newly identified target genes, our analysis showed that 16S rRNA, ompA and omcB were evolving in much the same way as our target genes.…”
Section: Resultsmentioning
confidence: 69%
“…In an attempt to understand these questions, Jackson et al, have previously performed fine-detailed epidemiological surveys of C. pecorum -infected koala populations, revealing that C. pecorum is genetically very diverse [7]. This analysis was performed on short variable domain IV (VDIV) sequence fragments of the omp A gene, encoding the surface-exposed major outer membrane protein (MOMP) which is common to all members of the Chlamydiaceae [15]. There are currently eight omp A VDIV genotypes that have been identified, following several studies of geographically isolated koala populations in Australia [7,8,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…While it has never been isolated from any animal but laboratory mice and hamsters (Zhang et al 1993), there is evidence of rodent chlamydial infection in nature (Ramsey et al 2016). Intravaginal inoculation with C. muridarum resembles an acute genital C. trachomatis infection in women.…”
Section: Animal Models Of Chlamydial Pathogenesismentioning
confidence: 99%